Current approaches to residual astigmatism correction after phacoemulsification - M.M. Bikbov; O.I. Orenburkina; A.E. Babushkin; A.M. Tulyakova (РМЖ "Клиническая офтальмология")
M.M. Bikbov, O.I. Orenburkina, A.E. Babushkin, A.M. Tulyakova Ufa Research Institute of Eye Diseases, Ufa, Russian Federation Residual astigmatism or ametropia are relatively common after phacoemulsification. This entity is accounted for by inaccurate intraocular lens (IOL) power calculation or improper preoperative examination. As a result, target refraction is not achieved. Spectacle correction of astigmatism in pseudophakia has several drawbacks and is often poorly tolerated, leaving patients unsatisfied with surgical outcomes. This paper reviews state-of-the-art surgical techniques for correcting residual astigmatism after cataract surgery. These include laser (photorefractive keratectomy/PRK and laser in situ keratomileusis/LASIK), Femto laser (arcuate keratotomy), and intraocular (add-on toric IOL implantation) procedures. The authors address published data on the pros and cons of these interventions. These techniques empower surgical correction of astigmatism and provide the best possible vision for patients. Finally, this paper discusses postoperative management using tear substitutes.  Keywords: phacoemulsification, residual astigmatism, PRK, LASIK, femtosecond arcuate incisions, add-on toric IOLs. For citation: Bikbov M.M., Orenburkina O.I., Babushkin A.E., Tulyakova A.M. Current approaches to residual astigmatism correction after phacoemulsification. Russian Journal of Clinical Ophthalmology. 2022;22(1):51–57 (in Russ.). DOI: 10.32364/2311-7729-2022-22-1-51-57.